Ammonia oxidation catalyst as well as preparation method and application thereof
By optimizing the proportion of active ingredient composition of the ammonia oxidation catalyst and selecting appropriate metal element components, the problems of reduced catalyst activity, high wear index and serious loss of molybdenum are solved, and the efficient, stable and economical performance of the catalyst is achieved.
Patent Information
- Application Number
- CN202411676988.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-04-01
AI Technical Summary
After long-term use, the catalytic activity of existing ammonia oxidation catalysts decreases, have high wear index, severe loss of molybdenum, and have low selectivity of catalysts and poor stability performance.
By optimizing the proportion of active ingredient composition of the catalyst, increasing the migration rate of lattice oxygen and the structural strength of the catalyst, the appropriate metal element components are selected to improve the anti-wear properties and economic benefits of the catalyst.
It significantly improves the catalytic performance of the catalyst, extends the service life of the catalyst, reduces the loss rate of molybdenum elements, and provides new performance evaluation indicators to improve the comprehensive performance of the catalyst.
Smart Images

Figure BDA0005147277380000241 
Figure BDA0005147277380000251
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalytic technology, and in particular to an ammonia oxidation catalyst and a preparation method and application thereof. Background Art
[0002] A large number of complex oxide catalysts containing molybdenum, bismuth and iron have been developed and used to produce acrolein, acrylic acid, acrylonitrile, acetonitrile, hydrocyanic acid and other substances. This process is a catalytic oxidation reaction of propylene under the conditions of ammonia and oxygen. In addition, it also includes the catalytic ammoxidation of propane to produce acrylonitrile, the catalytic ammoxidation of ethanol to produce acetonitrile, etc.
[0003] Chinese patent document CN115501882A discloses a catalyst for preparing acrylonitrile by propylene ammoxidation and its preparation method and application. The catalyst not only has a high acrylonitrile yield under a high propylene load, but also has a low acrolein yield, so that the acrylonitrile recovery rate of the device is high, the production efficiency and economic benefit of the device are improved, and it can be used in the industrial production of acrylonitrile. Chinese patent document CN1054914A discloses a fluidized bed catalyst for preparing acrylonitrile by propylene ammoxidation. In addition to having high activity and selectivity for the generation of acrylonitrile, the invention catalyst is more importantly suitable for catalytic reaction of air and propylene under low ratio conditions, thereby greatly increasing the production capacity of the reactor. Chinese patent document CN1379759A discloses a method for preparing acrylonitrile by propylene ammoxidation and obtaining a high yield and maintaining this effect for a long time. When the method uses propylene ammoxidation to generate acrylonitrile, a fluidized bed catalyst is used and a molybdenum-containing material is appropriately added while the reaction is being carried out. Chinese patent document CN101534945B discloses a fluidized bed catalyst for preparing acrylonitrile that can maintain a high acrylonitrile yield for a long time and a method for preparing acrylonitrile using the catalyst. Chinese patent document CN 101168129B discloses a catalyst for producing unsaturated nitrile by ammoxidation of olefins, which can produce unsaturated nitrile under the conditions of high catalyst load, high reaction pressure, low reaction temperature, low olefin ratio and low ammonia-olefin ratio. Chinese patent document CN107282064 B discloses a catalyst and preparation process for producing acrylonitrile, wherein the carrier uses silicon dioxide and a carrier modifier, which mainly solves the problems of low selectivity and poor stability of catalysts used for propylene ammoxidation reaction in the prior art.
[0004] Although the catalyst disclosed in the above patent document has greatly improved the yield of the main product in the initial stage of the reaction, it only proposes the combination of different metal source compounds in the ammonia oxidation catalyst, and does not clarify the catalytic mechanism of such multi-component catalyst and the influence of the combination of other metal elements other than molybdenum, bismuth and iron on the catalytic effect of ammonia oxidation; some of the added metal element combinations are obviously not suitable for oxidation reactions, but have a negative effect on the activity of the catalyst. Therefore, the currently known preparation methods of ammonia oxidation catalysts lack in-depth research on other metal elements other than molybdenum, bismuth and iron in the ammonia oxidation catalytic system.
[0005] In addition, there are some problems in the actual industrial use of ammonia oxidation catalysts, including:
[0006] 1. The yield of the reaction product is relatively high at the beginning of the operation of the catalyst, but after a certain period of operation, the product yield gradually begins to decrease. There are various reasons for this situation, including the design of the reactor, the control of reaction conditions, and the loss of catalyst in the fluidized bed reaction process. Among them, the loss in the fluidized bed reaction process is a key factor, because the catalyst particles are easy to collide and contact with each other in the fluidized reactor, which inevitably causes wear or breakage between the particles, thereby increasing the amount of fine powder in the reactor and being carried out by the reaction gas flow at the same time, resulting in the loss of the total amount of catalyst. Generally, once the wear index of a commercial catalyst exceeds 8.0, it means that the loss rate of the catalyst is high. For acrylonitrile catalysts, the wear index usually cannot exceed 4.0. The lower the value, the better the anti-wear performance and the longer the catalyst life. Therefore, preparing a catalyst with a low wear index is an important goal in the industry.
[0007] 2. In addition to wear and tear, molybdenum, as the main element of the catalyst, will undergo sublimation at the temperature of the ammonia oxidation catalytic reaction, resulting in a large loss of molybdenum in the catalyst system. Although some public patent documents have proposed a method of adding molybdenum-containing substances to the catalyst bed in a fluidized bed reactor, this method can restore the activity of part of the catalyst during the fluidized reaction and prolong the life of the catalyst. Although such methods can maintain the performance of the catalyst for a long time, the frequent addition of molybdenum-containing substances cannot solve the fundamental problem of large losses of the catalyst due to wear and tear. It will also cause the catalyst activity to gradually decrease with long-term use, and the operating cost will continue to increase. Therefore, improving the microstructural performance of the catalyst by utilizing the characteristics of different promoter metal elements can also help reduce the loss of molybdenum during the reaction process.
[0008] 3. When evaluating the performance of ammonia oxidation catalysts, taking acrylonitrile catalysts as an example, most of the patent literature technologies disclosed in the past are aimed at high conversion rate of propylene, high selectivity of acrylonitrile and high yield of acrylonitrile products, while also ensuring that the by-products acetonitrile and hydrocyanic acid are within a certain low yield range. In fact, this evaluation method needs to be adjusted in time according to the downstream sales market demand of different products in actual industrial applications, and ultimately the comprehensive performance of the catalyst is evaluated based on market demand and economic benefits. Summary of the invention
[0009] In view of the problems existing in the above-mentioned prior art, the present invention aims to provide a highly efficient ammoxidation catalyst and a preparation method thereof. For the catalytic reaction of ammoxidation of propylene, the composition ratio of the active components of the catalyst is regulated mainly from the action mechanism of the metal catalyst, which is not involved in the previous technology. On the one hand, the migration rate of lattice oxygen in the catalyst system is improved, and on the other hand, the structural strength of the catalyst is increased, and the anti-wear performance of the catalyst is correspondingly improved. Under certain preparation and synthesis conditions and certain reaction evaluation conditions, the comprehensive performance of the highly efficient ammoxidation catalyst of the present invention is evaluated, and it has a higher trinitrile product yield and a relatively low trinitrile production material consumption.
[0010] In order to achieve one of the above purposes, an ammonia oxidation catalyst is provided. The present invention adopts the following technical solution:
[0011] An ammonia oxidation catalyst, wherein the active component of the catalyst is composed of the general formula Mo x Bi a Fe b A c B d C e D f E g F h O y Indicates that, in the general formula:
[0012] Mo, Bi, Fe, O represent molybdenum, bismuth, iron and oxygen respectively;
[0013] A represents at least one element selected from the group consisting of nickel, cobalt, manganese, zinc and cadmium;
[0014] B represents at least one element selected from the group consisting of alkaline earth metal elements consisting of magnesium, strontium, and barium;
[0015] C represents at least one element selected from the group consisting of alkali metal elements consisting of potassium, rubidium, and cesium;
[0016] D represents at least one element selected from the group consisting of tungsten, vanadium, chromium, gallium, germanium, scandium, yttrium, indium, tin and antimony;
[0017] E represents at least one element selected arbitrarily from lanthanide elements except promethium;
[0018] F represents at least one element selected from the platinum group elements;
[0019] a, b, c, d, e, f, g, h and y are the atomic numbers of metal elements Bi, Fe, A, B, C, D, E, F and oxygen respectively;
[0020] x is the number of molybdenum atoms, and x is any integer greater than 1, which is used as a reference value;
[0021] The value of a is a multiple of x, and the multiple range of a is 0.03 to 0.07;
[0022] b is a multiple of x, and the multiple range of b is 0.12 to 0.31;
[0023] c is a multiple of x, and the multiple range of c is 0.3 to 0.5;
[0024] The value of d is a multiple of x, and the multiple range of d is 0.05 to 0.2;
[0025] The value of e is a multiple of x, and the range of multiples of e is 0.01 to 0.06;
[0026] The value of f is a multiple of x, and the range of multiples of f is 0.01 to 0.05;
[0027] The value of g is a multiple of x, and the range of multiples of g is 0.01 to 0.1;
[0028] h is a multiple of x, and the multiple range of h is 0.0001 to 0.001;
[0029] The value of y is the total number of oxygen atoms required to satisfy the compounds of each element in the catalyst.
[0030] Preferably, the atomic number relationship of each metal element is represented by the following formula:
[0031] M = (number of Mo atoms × 2) / (∑ number of atoms of other metal elements × valence of corresponding metal elements)
[0032] Wherein, M represents a proportional value obtained by dividing the product of the valence number of molybdate and the number of molybdenum atoms by the sum of the corresponding products of the corresponding valence numbers and the number of atoms of the remaining metal components;
[0033] The value range of M is 0.88~1.2.
[0034] Furthermore, the value of M is 0.93 to 1.05.
[0035] Preferably, B is one of magnesium and strontium; C is one of rubidium and cesium; D is one of tungsten and chromium; E is one of lanthanum and cerium; and F is one of platinum and ruthenium.
[0036] Preferably, the catalyst further comprises a carrier, and the amount of the carrier used accounts for 40 to 60 wt % of the total mass of the catalyst.
[0037] The second object of the present invention is to provide a method for preparing the ammonia oxidation catalyst, which comprises the following steps:
[0038] The raw materials of the metal elements constituting the catalyst and the carrier raw materials are mixed in advance to prepare an aqueous slurry, and then the obtained aqueous slurry is dehydrated and dried, and the obtained dry product is roasted to finally obtain a catalyst product.
[0039] Preferably, the raw materials of the metal elements are selected from the following forms of each metal element: oxide or nitrate, ammonium salt, hydroxide.
[0040] Preferably, the calcination temperature is 550-650° C. and the calcination time is 2-4 hours.
[0041] The third object of the present invention is to provide an application of the ammoxidation catalyst, wherein the catalyst is applied to the ammoxidation catalytic reaction of propylene, ammonia and oxygen. Under a certain reaction temperature and reaction pressure, propylene, ammonia and a gas containing molecular oxygen react in a fluidized bed reactor loaded with the catalyst to convert propylene into acrylonitrile, acetonitrile, hydrocyanic acid or other related products.
[0042] Beneficial effects of the present invention:
[0043] (1) The technical key of the catalyst of the present invention is that, from the perspective of reaction mechanism, the main roles of molybdenum and bismuth in the catalytic reaction of ammonia oxidation are clarified, and by optimizing and regulating the existing catalyst system by using other metal element components under a certain proportion relationship, the catalytic performance of the catalyst can be significantly improved, the yield of the product trinitrile can be increased, a high trinitrile yield can be maintained in the production of acrylonitrile, and the molybdenum loss rate is low.
[0044] (2) The technical key of the catalyst of the present invention is to maintain the migration rate of lattice oxygen in the catalyst system by regulating the proportion of specific metal oxides in the catalyst. The selection of metal elements must follow three principles and the order of priority under the premise of not affecting the performance of the catalyst: variable valence metals > metals with ionic radius not greater than the bismuth ion radius > metals with empty d electron orbitals. By selecting metals in the above manner, under a certain proportion regulation, the activity of the catalyst and the yield of the product trinitrile can be significantly improved.
[0045] (3) The key to the catalyst of the present invention is to add a small proportion of auxiliary metal elements, which can improve the dispersion of key elements of the catalyst, avoid coking of the catalyst during calcination, enhance the structural stability of the catalyst, and increase the specific surface area of the catalyst, etc., such as adding a small amount of alkali metals, alkaline earth metals, transition metal elements, rare metals, etc. In addition, the present invention also proposes that metal elements such as lithium, sodium, titanium, zirconium, aluminum, etc. should be avoided in the catalyst system. Such metal elements are prone to polymerization in the catalyst system, which reduces the catalytic activity.
[0046] (4) The key to the catalyst of the present invention is that new performance evaluation indicators are proposed, including the total yield of three nitrile products, the material consumption of three nitrile output and the material consumption of three nitrile output value. Instead of using only the acrylonitrile yield and propylene conversion rate as the performance evaluation indicators of the catalyst, the total yield of the three nitrile products and the overall economic benefits are fully considered, which can not only provide a new comprehensive performance evaluation standard for the catalyst, but also take into account the economic applicability of the catalyst. DETAILED DESCRIPTION
[0047] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually performed under conventional conditions or according to the conditions recommended by the manufacturer. Unless otherwise defined, all professional and scientific terms used in the text have the same meanings as those familiar to those skilled in the art. In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention. The preferred implementation methods and materials described in the text are for demonstration purposes only.
[0048] Unless otherwise specified, "%" in the present invention refers to mass percentage. The materials used as raw materials in the examples were purchased.
[0049] In order to further understand the present invention, before providing the specific embodiments of the present invention, based on the in-depth research on metal catalysts in the technical field, combined with the latest ammoxidation catalytic mechanism currently recognized internationally, the reaction mechanism of the catalyst of the present invention catalyzing the ammoxidation of propylene to produce acrylonitrile, acetonitrile, hydrocyanic acid and other products is as follows:
[0050] Physical adsorption occurs at the [Bi] site of the catalyst, including the adsorption of propylene, ammonia, intermediates, acrylonitrile, acetonitrile, hydrocyanic acid and other by-product molecules, by providing the electron density of the lone electron pairs on the above molecules to the under-coordinated Bi cation. Taking the process of propylene adsorption and dehydrogenation as an example, the propylene molecule adsorbed on the [Bi] site has a hydrogen atom taken away by the adjacent site [Mo=O] site to form [Mo-OH], and the remaining π-allyl radical continues to be adsorbed on the [Bi] site; [Mo-OH] is oxidized by external oxygen molecules (hereinafter referred to as "lattice oxygen") and then dehydrated and restored to the [Mo=O] form. This process is called "lattice oxygen migration"; the π-allyl radical adsorbed on the Bi site combines with the adjacent [Mo=O] to form [Mo-O-CH2-CH=CH2]; further, under certain conditions of the presence of ammonia, ammonia molecules are also adsorbed on the surface of the [Bi] site, and the ammonia molecules adsorbed on the [Bi] site react with the [Mo-O-CH2-CH=CH2] formed after the dehydrogenation of propylene to generate the intermediate product allylamine (CH2=CH-CH2 -NH2); the intermediate product allylamine continues to be adsorbed on the [Bi] site, and a hydrogen atom is captured by the adjacent [Mo=O] site, and then further combines with another adjacent [Mo=O] site to form [Mo-O-CHNH2-CH=CH2]; the intermediate substance on the [Mo] site is further captured three hydrogen atoms by three different adjacent [Mo=O] sites for three consecutive times to form [Mo-O-CN-CH=CH2], and during these three dehydrogenation processes, [Mo-OH] is oxidized to [Mo=O] by lattice oxygen each time, and the hydrogen atoms are released in the form of water; and then further, acrylonitrile (CH2=CH-C≡N) is separated from the [Mo] site, and the [Mo] site becomes a reduced state, which is further oxidized by lattice oxygen and dehydrated to [Mo=O] form, and finally the catalyst returns to its initial form. The formation mechanism of acetonitrile and hydrocyanic acid is similar to that of acrylonitrile, except that another ammonia molecule adsorbed on the [Bi] site reacts with the allylamine group [Mo-O-CHNH2-CH=CH2] on the [Mo] site to form [Mo-O-CHNH2-CHNH2-CH3]; then the carbon-carbon double bond breaks, forming [Mo-O-CHNH2] at the original [Mo] site, and [-CHNH2-CH3] combines with the adjacent new [Mo=O] to form [Mo-O-CHNH2-CH3]; further, the latter undergoes two dehydrogenation reactions, and acetonitrile (CN-CH3) detaches from the new [Mo=O]; while the former undergoes two dehydrogenation reactions, and hydrocyanic acid (HCN) detaches from the original [Mo] site; and the two [Mo] sites after desorption become reduced states, which can be further oxidized by lattice oxygen and then dehydrated to [Mo=O] form, and finally the catalyst returns to its initial form. The above is the formation mechanism of the trinitrile.
[0051] From the above reaction mechanism, it can be seen that under the catalytic action of the catalyst, propylene undergoes an ammoxidation reaction at the bismuth-molybdenum site in the presence of lattice oxygen and ammonia, and further reacts with the intermediate product allylamine to eventually generate acrylonitrile products and byproducts acetonitrile and hydrocyanic acid. If there is an excess of external oxygen molecules (lattice oxygen), an oxidation reaction will also occur to generate other organic and inorganic oxygen-containing compounds, such as acrolein, acrylic acid, carbon dioxide, carbon monoxide and other byproducts. Therefore, it is particularly important to control the amount of lattice oxygen in the catalytic system.
[0052] Furthermore, it can be concluded from the above mechanism that the main reactions are all generated by adjacent [Mo] sites. The original [Mo=O] is transformed into [Mo-OH] after extracting [H], and then restored to [Mo=O] form after being oxidized by lattice oxygen, while the [H] atom escapes in the form of water molecules. This process can be summarized as a series of cyclic reactions such as hydrogen abstraction, oxidation, dehydration, and lattice oxygen restoration on [Mo=O], and the oxidation-dehydration reaction process provides the thermodynamic driving force for the overall cyclic reaction. Therefore, lattice oxygen migration is the most critical factor in this catalyst system besides the key active elements of molybdenum and bismuth. It can not only improve the catalyst performance, but also the faster migration rate can help reduce the structural distortion of the catalyst during the reaction.
[0053] Controlling the lattice oxygen migration rate in the catalytic system depends on the composition and crystal phase structure of the different metal oxides in the catalyst system. For example, the metal bonds of the transition metal elements in the catalyst have certain d-band electron holes. This ability to gain and lose electrons can not only accelerate electron transfer, but also improve the chemical adsorption capacity of the catalyst, which is more conducive to the migration of lattice oxygen. For example, the size of the ionic radius of the divalent and trivalent metal ions in the catalyst will also affect the migration rate of lattice oxygen. When the ionic radius is close and lower than the bismuth ion radius, the migration rate of lattice oxygen will be affected. In the case of , the divalent metal ions in the catalyst are easily replaced by trivalent metal ions, thereby increasing the migration rate of lattice oxygen. n+ / M (n+1)+ ) Redox pairs, oxygen vacancies on the surface of reduced metals can also accelerate the transfer of electrons and lattice oxygen. Among these metal elements, iron is a common typical element, so iron must be present in the catalyst system. In addition, there are a small amount of auxiliary metal elements in the catalyst, whose functions include improving the dispersion of key elements of the catalyst, preventing the catalyst from coking, enhancing the structural stability of the catalyst, and increasing the specific surface area of the catalyst.
[0054] Therefore, it is very important to optimize the formulation composition of the catalyst and the crystal phase structure during the catalyst preparation process. The present invention conducts in-depth research on the fluidized bed catalyst for ammoxidation reaction disclosed at home and abroad and the recognized catalytic reaction mechanism, and combines experimental research to adjust the composition of different metal oxide components in the catalyst and the ammoxidation catalyst product prepared by a specific ratio under a specific synthesis method, which can not only achieve a high trinitrile yield for a long time, but also reduce the loss rate of molybdenum-containing substances.
[0055] Based on the mechanism study of lattice oxygen migration rate, as a preferred embodiment of the present invention, it is an ammonia oxidation catalyst, the active component of the catalyst is composed of the general formula Mo x Bi a Fe b A c B d C e D f E g F h O y Indicates that, in the general formula:
[0056] Mo, Bi, Fe, O represent molybdenum, bismuth, iron, and oxygen, respectively;
[0057] A represents at least one element selected from the group consisting of nickel, cobalt, manganese, zinc and cadmium;
[0058] B represents at least one element selected from the alkaline earth metal element combination consisting of magnesium, strontium and barium, such as at least one element selected from the combination consisting of magnesium, strontium and barium; preferably, B is one of magnesium and strontium;
[0059] C represents at least one element selected from the group consisting of potassium, rubidium and cesium, such as at least one element selected from the group consisting of potassium, rubidium and cesium; preferably, one of rubidium and cesium;
[0060] D is at least one element selected from the group consisting of tungsten, vanadium, chromium, gallium, germanium, scandium, yttrium, indium, tin and antimony; preferably, D is one of tungsten and chromium;
[0061] E represents at least one element selected arbitrarily from the lanthanide elements except promethium; preferably, E is one of lanthanum and cerium;
[0062] F represents at least one element selected from the platinum group elements; preferably, F is one of platinum and ruthenium.
[0063] For the active component Mo x Bi a Fe b A c B d C e D f E g F h O y For example, a, b, c, d, e, f, g, h and y are the atomic numbers of Bi, Fe, A, B, C, D, E, F metal elements and oxygen respectively;
[0064] x is the number of molybdenum atoms and x is any integer greater than 1, which is used as a reference value;
[0065] The value of a is a multiple of x, and the multiple range of a is 0.03 to 0.07;
[0066] b is a multiple of x, and the multiple range of b is 0.12 to 0.31;
[0067] c is a multiple of x, and the multiple range of c is 0.3 to 0.5;
[0068] The value of d is a multiple of x, and the multiple range of d is 0.05 to 0.2;
[0069] The value of e is a multiple of x, and the range of multiples of e is 0.01 to 0.06;
[0070] The value of f is a multiple of x, and the range of multiples of f is 0.01 to 0.05;
[0071] The value of g is a multiple of x, and the range of multiples of g is 0.01 to 0.1;
[0072] h is a multiple of x, and the multiple range of h is 0.0001 to 0.001;
[0073] The value of y is the total number of oxygen atoms required to satisfy the compounds of each element in the catalyst.
[0074] The atomic number relationship of the above metal elements is expressed by the following formula:
[0075] M = (number of Mo atoms × 2) / ∑ (number of atoms of other metal elements × valence of corresponding metal elements)
[0076] Wherein, M represents the ratio value obtained by dividing the product of the valence number of molybdate and the number of molybdenum atoms by the sum of the corresponding products of the corresponding valence numbers and atomic ratios of the remaining metal components; if the value of M is less than 1, it means that the Mo content in the catalyst system is relatively small; if the value of M is greater than 1, it means that the Mo content in the catalyst system is relatively high. The value range of M is 0.88 to 1.2M. Preferably, the value is 0.93 to 1.05.
[0077] Based on this implementation mode, the addition of an appropriate amount of metal element A not only effectively improves the specific surface area and stability of the catalyst as a structural additive, but also forms a solid solution phase with bismuth molybdate salt during the catalyst calcination process, which helps to improve the catalyst's selectivity for light olefins; the addition of a small amount of alkaline earth metal B can strengthen the interaction between metal oxides such as molybdenum, bismuth, and iron and the silica sol carrier, which is beneficial to promote the uniform dispersion of other active components on the carrier surface, thereby improving the activity of the catalyst; the addition of an appropriate amount of alkali metal element C can not only help the catalyst eliminate acid sites, but also is beneficial to the migration rate of lattice oxygen, because its ionic radius is relatively large, during the catalyst calcination During the activation process, the lattice is easily distorted and ion vacancies are generated at the same time, which enhances the conductivity. However, the amount of alkali metal elements added should not be too high, which can easily cause serious distortion of the catalyst and reduce the activity. Metal element D, as an electron auxiliary agent, has electron holes and electron-dense areas. The appropriate amount of addition can reduce the electron escape of the catalyst, which is beneficial to the adsorption of reactants (propylene, ammonia) and intermediates and the desorption of products, further improving the performance of the catalyst. The trace addition of lanthanide metal E is conducive to promoting the dispersion of elements such as iron and nickel, and lanthanide metal oxides can delay the growth and sintering of catalyst grains during the calcination process, further improving the stability of the catalyst. In addition, the multivalent state of cerium can promote the migration of electrons in the catalyst, which is beneficial to the increase of the migration rate of lattice oxygen and the reaction activity. The trace addition of platinum group metal F helps to extend the life of the catalyst. Due to the high melting point and high density of platinum group metal elements, the thermal stability and wear resistance of the catalyst can be further improved. Thus, the present invention is based on the construction of an appropriate catalytic system and controls the action of lattice oxygen in the catalytic system, which can significantly improve the catalyst performance and reduce the structural distortion of the catalyst produced during the reaction, thereby obtaining a higher trinitrile product yield and a relatively low trinitrile production material consumption.
[0078] The catalyst also includes a carrier, and the amount of the carrier used accounts for 40-60wt% of the total mass of the catalyst. Preferably, it is 45-55wt%. The carrier uses a silica raw material, preferably colloidal silica (also known as "silica sol"). Silica sol can be selected from commercial products. The selection specifications of silica sol are as follows:
[0079] The content of silicon dioxide is 30-50wt%, preferably 33-41wt%;
[0080] The average particle size ranges from 2 to 100 nm, preferably from 10 to 30 nm, and the particle size distribution may be multiple peaks, with a single peak being the most preferred;
[0081] The specific surface area ranges from 80 to 200 m 2 / g, preferably 100-150m 2 / g;
[0082] The viscosity ranges from 8 to 15 cp (@25°C), preferably from 10 to 12 cp (@25°C).
[0083] The pH value ranges from 7 to 9.5, preferably from 8 to 9;
[0084] The ion type is an ammonium ion stable type, and the sodium ion stable type should be avoided, because the polymerization effect of sodium ions is not applicable in the catalyst system of the present invention, on the contrary, it will have a negative effect and affect the activity of the catalyst.
[0085] The commercially available silica sol products mentioned above can be used as a single carrier or in combination of multiple products.
[0086] As another preferred embodiment of the present invention, a method for preparing an ammonia oxidation catalyst comprises the following steps:
[0087] The raw materials of the metal elements constituting the catalyst and the carrier raw materials are mixed in advance to prepare an aqueous slurry. The aqueous slurry is prepared according to the active phase composition of the catalyst, and then the obtained aqueous slurry is dehydrated and dried, and the obtained dry product is roasted to finally obtain a catalyst product.
[0088] The raw materials of the metal elements are oxides of the metal elements or nitrates, ammonium salts, and hydroxides that are easily converted into oxides. The specific raw materials of the metal elements are as follows:
[0089] As the raw material of the molybdenum component, there can be mentioned ammonium metamolybdate, ammonium tetramolybdate, ammonium dimolybdate, molybdenum trioxide and molybdenum dioxide.
[0090] The raw material of the bismuth component may be bismuth nitrate or bismuth oxide.
[0091] The raw material of the iron component may be iron nitrate, iron oxide or iron hydroxide.
[0092] The raw material of the nickel component may be nickel nitrate, nickel oxide or nickel hydroxide.
[0093] The raw material of the magnesium component may be nickel nitrate, nickel oxide or nickel hydroxide.
[0094] The raw materials of other metal element components may be nitrates, ammonium salts, oxides and hydroxides of the metal elements.
[0095] According to actual needs, the raw materials of the above-mentioned metal elements can be combined in various ways.
[0096] The dehydration and drying method of the aqueous slurry is to convert the aqueous slurry into a fine particle product in the shape of microspheres, that is, a catalyst semi-finished product, and evaporate and remove about 90-95% of the water at the same time. In order to obtain solid particles with easier control of particle size distribution, a spray dryer is preferably used. The spraying method can be a pressure nozzle, an airflow nozzle, or a rotary atomizer. A rotary atomizer is preferred, which can obtain solid particles with more uniform particle size distribution; specifically, the slurry is sent to a high-speed rotating dispersion disk by a pump, and the liquid is pulled into a thin film on the rotating surface due to the centrifugal force, and is thrown out from the edge of the dispersion disk at an increasing speed to form droplets. The circumferential speed of the dispersion disk is preferably in the range of 90-140m / s. The droplets can be dried into solid particles at an operating temperature of 250-350°C. The parameters of spray drying directly affect the physical properties of the catalyst such as particle size distribution and bulk density; selecting appropriate spray drying conditions is conducive to controlling the particle size distribution of the catalyst, including the rotation speed of the sprayer, the feed rate, the air volume of the fan, the inlet and outlet air temperature and other operating conditions, and the specific parameters are as follows:
[0097] Atomizer turntable rotation speed: 35~55Hz;
[0098] Feed rate: 5-15 mL / min;
[0099] Fan air intake: 50~250m 3 / h
[0100] Inlet air temperature: 280~350℃;
[0101] Air outlet temperature: 150~190℃.
[0102] The calcination method refers to calcining the solid fine particle product after spray drying, i.e., the catalyst semi-finished product, at a high temperature, and further obtaining a finished catalyst product with a certain specific surface area, pore volume, pore structure and active phase. The calcination temperature and calcination time directly determine the performance of the catalyst. For example, if the calcination temperature is too low or the calcination time is too short, the optimal activity of the catalyst has not been fully formed; on the contrary, if the calcination temperature is too high or the calcination time is too long, the optimal active phase will be destroyed. Both situations will result in a decrease in product yield and an increase in the total amount of by-products.
[0103] The calcination time is controlled within 1 to 6 hours, and the preferred calcination time is 2 to 4 hours.
[0104] The calcination temperature is controlled within the range of 550-700°C, and the preferred calcination temperature is 590-650°C.
[0105] To further improve the catalytic activity:
[0106] A two-stage calcination method can be used, with a pre-heat treatment at 200-450°C for 1-3 hours to decompose the remaining water, nitrates, etc. in the catalyst raw material, and then calcination at a temperature in the range of 550-700°C.
[0107] Furthermore, a three-stage calcination method can be adopted, pre-heat treatment at a temperature of 200-450°C for 1-3 hours, then heat treatment at a temperature of 450-550°C for 1-3 hours, to fully decompose the remaining moisture, nitrates, etc. in the catalyst raw material, and finally calcination at a temperature in the range of 550-700°C.
[0108] The calcination method is preferably a rotary calcination furnace or a fluid calcination furnace, which ensures that the catalyst particles are in a relatively gentle motion state during the calcination process to prevent the catalyst from agglomerating during the calcination process.
[0109] Preferably, a flowing oxygen-containing atmosphere, preferably air, is used during the calcination process; the catalyst is fully contacted with the flowing air, further promoting the formation of oxides or molybdates with a certain phase structure inside the catalyst particles, and the flowing air can carry away gaseous nitrogen oxides released from the catalyst during the calcination process.
[0110] Based on the above, the preferred preparation method of the present invention can be: heating deionized water to 65-85°C, adding a certain amount of ammonium metamolybdate in small amounts and multiple times under uniform stirring, stirring continuously until completely dissolved, cooling for standby use, obtaining a molybdenum-based mother liquor, and maintaining the temperature between 45 and 65°C. Then prepare silica sol to form a carrier liquid. Then add the prepared carrier liquid to the molybdenum-based mother liquor at a certain addition rate, stirring continuously at a uniform speed during the addition process to form an initial slurry, and maintaining the temperature range between 55 and 65°C. Then prepare another portion of deionized water and heat it to 65-85°C, add the raw materials of other metal elements in turn under uniform stirring, stirring continuously until completely dissolved, cooling for standby use, obtaining a soluble metal salt solution, and maintaining the temperature between 45 and 65°C. Add the prepared soluble metal salt solution to the initial slurry at a certain addition rate, heat the temperature to 75-85°C during the addition process, and continue to stir at a uniform speed until the soluble metal salt solution is completely mixed with the initial slurry. The mixture is then heated to 102-108°C and aged for about 10-20 minutes at this temperature to finally form a catalyst precursor slurry, which is then stored at 65-85°C for later use.
[0111] Then, start the spray dryer, preheat the outlet air temperature to 160-180°C, deliver the catalyst precursor slurry prepared above to the top of the spray dryer at a certain feed rate (e.g., 8-12 mL per minute), and atomize and dry the slurry at a turntable speed of 40-50 Hz to form microsphere particles.
[0112] Next, the sprayed microsphere particles are placed in a rotary calcining furnace, the furnace body is rotated at a certain speed in a small amount of air circulation atmosphere, and the particles are first calcined at 200-220°C for 30 minutes, then calcined at 400-420°C for 120 minutes, and finally calcined at 600-670°C for 4 hours to complete the catalyst molding preparation. Finally, the catalyst product of the present invention is obtained.
[0113] As another embodiment of the present invention, an ammoxidation catalyst prepared based on the above embodiment of the present invention is used in the ammoxidation catalytic reaction of propylene, ammonia and oxygen. Under a certain reaction temperature and reaction pressure, propylene, ammonia and a gas containing molecular oxygen react in a fluidized bed reactor filled with the catalyst to convert propylene into acrylonitrile, acetonitrile, hydrocyanic acid or other related products. Among them, the fluidized bed reactor is a recognized prior art.
[0114] The performance evaluation of the catalyst of the present invention can be carried out in a fluidized bed reactor with a diameter of 1.5 feet, and the reaction conditions are:
[0115] Reaction temperature: 420~440℃;
[0116] Reaction pressure: 80~140kPa;
[0117] Raw material molar ratio: propylene / ammonia / air (calculated as oxygen) = 1 / (1.05-1.3) / (1.5-2.5);
[0118] Catalyst filling amount: 400-550g;
[0119] Catalyst load (WWH): 0.06~0.14hr -1 , preferably 0.08 to 0.11 hr -1 .
[0120] Based on the actual application requirements of the ammoxidation catalyst, the indicators for evaluating the performance of the catalyst in the present invention include the total yield of trinitrile, the material consumption of trinitrile output and the material consumption of trinitrile output value. The three indicators are specifically as follows:
[0121] Total yield of trinitriles (%) = acrylonitrile yield + acetonitrile yield + hydrocyanic acid yield
[0122] Consumption of trinitrile production (g / g) = propylene consumption / (acrylonitrile production + acetonitrile production + hydrocyanic acid production)
[0123] Consumption of trinitrile output (g / yuan) = propylene consumption / (acrylonitrile output + acetonitrile output + hydrocyanic acid output)
[0124] In the above formula,
[0125] Acrylonitrile yield refers to the molar percentage yield of acrylonitrile, and the calculation formula is as follows:
[0126] Acrylonitrile yield (mol%) = (mol number of acrylonitrile generated / mol number of propylene fed) × 100. Acetonitrile yield refers to the molar percentage yield of acetonitrile, calculated as follows:
[0127] Acetonitrile yield (mol%) = (mol number of acetonitrile produced / mol number of propylene fed) × 100
[0128] The hydrocyanic acid yield refers to the molar percentage yield of hydrocyanic acid, and the calculation formula is as follows:
[0129] Hydrocyanic acid yield (mol%) = (molar number of hydrocyanic acid generated / molar number of propylene fed) × 100 Propylene consumption refers to the feed flow rate of propylene in the reactor, g / h.
[0130] The acrylonitrile yield, acetonitrile yield and hydrocyanic acid yield refer to the yield of each product, respectively. In the present invention, it refers to the calculated value obtained by the molar number of each product generated after the reaction in the reactor, g / h.
[0131] The output value of acrylonitrile, acetonitrile and hydrocyanic acid refers to the product of each output and the current market price. It should be noted that due to market price fluctuations, the present invention only provides a new economic indicator evaluation method for ammonia oxidation catalysts, and the output value of each product and the consumption of trinitrile output value are not calculated in the evaluation results of the relevant embodiments.
[0132] Based on the above embodiments, specific examples are provided:
[0133] Example 1
[0134] 1. Preparation and Forming Process of the Catalyst of the Present Invention
[0135] Heat 200mL of deionized water to 65-85°C, add a total of 250g of ammonium metamolybdate in small amounts and multiple times under uniform stirring, continue stirring until completely dissolved, cool down for standby use, obtain a molybdenum-based mother liquor, and keep the temperature between 45 and 65°C. Then prepare 350g of a silica sol with a silica content of 30% and 350g of a silica sol with a silica content of 41%, and mix the two silica sols evenly to form a carrier liquid. Then add the prepared carrier liquid to the molybdenum-based mother liquor at a rate of 10mL per minute, continue stirring at a uniform speed during the addition process to form an initial slurry, and maintain the temperature range between 55 and 65°C. Then prepare another 100mL of deionized water and heat it to 65-85°C. Add 90g of ferric nitrate 9hydrate, 28g of bismuth nitrate pentahydrate, 160g of nickel nitrate hexahydrate, 55g of magnesium nitrate hexahydrate, 50g of cerium nitrate hexahydrate, 10g of chromium nitrate 9hydrate, 8g of potassium nitrate and 0.1g of ruthenium nitrate in sequence under uniform stirring, continue stirring until completely dissolved, cool down for standby use, obtain a soluble metal salt solution, and keep the temperature between 45 and 65°C. Add the prepared soluble metal salt solution to the initial slurry at a rate of 10mL per minute, heat the temperature to 75-85°C during the addition process, and continue to stir at a uniform speed until the soluble metal salt solution is completely mixed with the initial slurry. Then heat to 102-108°C, age the slurry at this temperature for about 10-20 minutes, and finally form a catalyst precursor slurry, which is stored at 65-85°C for standby use.
[0136] Start the spray dryer, preheat the outlet air temperature to 160-180°C, deliver the catalyst precursor slurry to the top of the spray dryer at a feed rate of 8-12 mL per minute, and form microsphere particles after atomization and drying of the slurry at a turntable speed of 40-50 Hz. Put the sprayed microsphere particles into a rotary calcining furnace, rotate the furnace body at a speed of 5 rpm in a small amount of air circulation atmosphere, first calcine at 200-220°C for 30 minutes, then calcine at 400-420°C for 120 minutes, and finally calcine at 600-670°C for 4 hours to complete the catalyst molding preparation. Finally, the catalyst product of the present invention is obtained.
[0137] The expression of the active composition of the catalyst prepared by the above-mentioned preparation and molding method is as follows:
[0138] Mo x Bi 0.04x Fe 0.16x Ni 0.39x Mg 0.15x K 0.056x Cr(Ⅲ) 0.018x Ce(Ⅲ) 0.08x Ru 0.0002x O 4x
[0139] 2. Catalyst performance evaluation
[0140] The catalyst obtained in this embodiment was evaluated and tested in a 1.5-foot fluidized bed reactor. The operating temperature of the reactor was 435±5°C, the operating pressure was 80±5KPa, and the molar ratio of propylene / ammonia / air was 1 / 1.2 / 9.5. The filling amount of the catalyst was 440±5g. The catalyst load of propylene was 0.08WWH. After a stable period of reaction for more than 20 hours, the reaction products were collected and product analysis tests were performed. After a long-term evaluation test, the final evaluation results were obtained (the stability test of the product yield was started after the reaction reached 20 hours, and the final product yield after 400 hours of continuous operation was taken as the test results of each embodiment of the present invention).
[0141] The active components and performance evaluation results of the catalyst are shown in Table 1.
[0142] Example 2
[0143] Except that the amount of nickel nitrate hexahydrate added in the composition of the soluble metal salt solution was reduced by 60 g, and 40 g of cobalt nitrate hexahydrate was added, the other catalyst preparation and molding methods were the same as those in Example 1. The expression of the active composition of the prepared catalyst is as follows:
[0144] Mo x Bi 0.04x Fe 0.16x Ni 0.24x Mg 0.15x Co 0.1x K 0.056x Cr(Ⅲ) 0.018x Ce(Ⅲ) 0.08x Ru 0.0002x O 4x
[0145] The catalyst performance evaluation methods are the same as those in Example 1.
[0146] The active components and performance evaluation results of the catalyst are shown in Table 1.
[0147] Example 3
[0148] Except that the amount of nickel nitrate hexahydrate added in the composition of the soluble metal salt solution was reduced by 40 g, and 30 g of manganese nitrate was added, the other catalyst preparation and molding methods were the same as those in Example 1. The expression of the active composition of the prepared catalyst is as follows:
[0149] Mo x Bi 0.04x Fe 0.16x Ni 0.29x Mg 0.15x Mn 0.12x K0.056x Cr(Ⅲ) 0.018x Ce(Ⅲ) 0.08x Ru 0.0002x O 4x
[0150] The catalyst performance evaluation methods are the same as those in Example 1.
[0151] The active components and performance evaluation results of the catalyst are shown in Table 1.
[0152] Example 4
[0153] Except that the dosage of magnesium nitrate hexahydrate is reduced by 25 g in the composition of the soluble metal salt solution, and 15 g of strontium nitrate is added, the other catalyst preparation and molding methods are the same as those in Example 1. The expression of the active composition of the prepared catalyst is as follows:
[0154] Mo x Bi 0.04x Fe 0.16x Ni 0.39x Mg 0.08x Sr 0.05x K 0.056x Cr(Ⅲ) 0.018x Ce(Ⅲ) 0.08x Ru 0.0002x O 4x The catalyst performance evaluation methods are the same as those in Example 1.
[0155] The active components and performance evaluation results of the catalyst are shown in Table 1.
[0156] Example 5
[0157] Except that the amount of potassium nitrate added in the soluble metal salt solution was reduced by 8 g and 5 g of rubidium nitrate was added, the other catalyst preparation and molding methods were the same as those in Example 1. The expression of the active composition of the prepared catalyst is as follows:
[0158] Mo x Bi 0.04x Fe 0.16x Ni 0.39x Mg 0.15x R 0.024x Cr(Ⅲ) 0.018x Ce(Ⅲ) 0.08x Ru 0.0002x O 4x
[0159] The catalyst performance evaluation methods are the same as those in Example 1.
[0160] The active components and performance evaluation results of the catalyst are shown in Table 1.
[0161] Example 6
[0162] Except that the dosage of rubidium nitrate was reduced by 5 g in the composition of the soluble metal salt solution, and 5 g of cesium nitrate was added, the other catalyst preparation and molding methods were the same as those in Example 1. The expression of the active composition of the prepared catalyst is as follows:
[0163] Mo x Bi 0.04x Fe 0.16x Ni 0.39x Mg 0.15x Cs 0.018x Cr(Ⅲ) 0.018x Ce(Ⅲ) 0.08x Ru 0.0002x O 4x
[0164] The catalyst performance evaluation methods are the same as those in Example 1.
[0165] The active components and performance evaluation results of the catalyst are shown in Table 1.
[0166] Example 7
[0167] Except that the dosage of chromium nitrate nonahydrate was reduced by 3 g in the composition of the soluble metal salt solution, and 1 g of chromium trioxide was added, the other catalyst preparation and molding methods were the same as those in Example 1. The expression of the active composition of the prepared catalyst is as follows:
[0168] Mo x Bi 0.04x Fe 0.16x Ni 0.39x Mg 0.15x R 0.024x Cr(Ⅲ) 0.012x Cr(VI) 0.007x Ce(Ⅲ) 0.08x Ru 0.0002x O 4x The catalyst performance evaluation methods are the same as those in Example 1.
[0169] The active components and performance evaluation results of the catalyst are shown in Table 1.
[0170] Example 8
[0171] Except that the dosage of chromium nitrate nonahydrate was reduced by 5 g in the composition of the soluble metal salt solution, and 2 g of chromium trioxide was added, the other catalyst preparation and molding methods were the same as those in Example 1. The expression of the active composition of the prepared catalyst is as follows:
[0172] Mo x Bi 0.04x Fe 0.16x Ni 0.39x Mg0.15x R 0.024x Cr(Ⅲ) 0.009x Cr(VI) 0.014x Ce(Ⅲ) 0.08x Ru 0.0002x O 4x
[0173] The catalyst performance evaluation methods are the same as those in Example 1.
[0174] The active components and performance evaluation results of the catalyst are shown in Table 1.
[0175] Example 9
[0176] Except that the dosage of chromium nitrate nonahydrate was reduced by 8 g in the composition of the soluble metal salt solution, and 3 g of chromium trioxide was added, the other catalyst preparation and molding methods were the same as those in Example 1. The expression of the active composition of the prepared catalyst is as follows:
[0177] Mo x Bi 0.04x Fe 0.16x Ni 0.39x Mg 0.15x R 0.024x Cr(Ⅲ) 0.004x Cr(VI) 0.021x Ce(Ⅲ) 0.08x Ru 0.0002x O 4.1x
[0178] The catalyst performance evaluation methods are the same as those in Example 1.
[0179] The active components and performance evaluation results of the catalyst are shown in Table 1.
[0180] Example 10
[0181] Except that the dosage of chromium nitrate nonahydrate is reduced by 10 g in the composition of the soluble metal salt solution, and 5 g of chromium trioxide is added, the other catalyst preparation and molding methods are the same as those in Example 1. The expression of the active composition of the prepared catalyst is as follows:
[0182] Mo x Bi 0.04x Fe 0.16x Ni 0.39x Mg 0.15x R 0.024x Cr(VI) 0.035x Ce(Ⅲ) 0.08x Ru 0.0002x O 4.1x
[0183] The catalyst performance evaluation methods are the same as those in Example 1.
[0184] The active components and performance evaluation results of the catalyst are shown in Table 1.
[0185] Embodiment 11
[0186] Except that the dosage of cerium nitrate hexahydrate is reduced by 20 g in the composition of the soluble metal salt solution, and 10 g of ammonium cerium nitrate is added, the other catalyst preparation and molding methods are the same as those in Example 10. The expression of the active composition of the prepared catalyst is as follows:
[0187] Mo x Bi 0.04x Fe 0.16x Ni 0.39x Mg 0.15x R 0.024x Cr(VI) 0.035x Ce(Ⅲ) 0.049x Ce(Ⅳ) 0.013x Ru 0.0002x O 4.1x The catalyst performance evaluation methods are the same as those in Example 10.
[0188] The active components and performance evaluation results of the catalyst are shown in Table 1.
[0189] Example 12
[0190] Except that the dosage of cerium nitrate hexahydrate is reduced by 30 g in the composition of the soluble metal salt solution, and 20 g of ammonium cerium nitrate is added, the other catalyst preparation and molding methods are the same as those in Example 10. The expression of the active composition of the prepared catalyst is as follows:
[0191] Mo x Bi 0.04x Fe 0.16x Ni 0.39x Mg 0.15x R 0.024x Cr(VI) 0.035x Ce(Ⅲ) 0.033x Ce(Ⅳ) 0.026x Ru 0.0002x O 4.1x
[0192] The catalyst performance evaluation methods are the same as those in Example 10.
[0193] The active components and performance evaluation results of the catalyst are shown in Table 1.
[0194] Example 13
[0195] Except that the dosage of cerium nitrate hexahydrate is reduced by 40 g in the composition of the soluble metal salt solution, and 30 g of ammonium cerium nitrate is added, the other catalyst preparation and molding methods are the same as those in Example 10. The expression of the active composition of the prepared catalyst is as follows:
[0196] Mo x Bi 0.04x Fe 0.16x Ni 0.39x Mg 0.15x R 0.024x Cr(VI) 0.035x Ce(Ⅲ) 0.016x Ce(Ⅳ) 0.039x Ru 0.0002x O 4.1x
[0197] The catalyst performance evaluation methods are the same as those in Example 10.
[0198] The active components and performance evaluation results of the catalyst are shown in Table 1.
[0199] Embodiment 14
[0200] Except that the dosage of cerium nitrate hexahydrate is reduced by 10 g in the composition of the soluble metal salt solution, and 10 g of lanthanum nitrate is added, the other catalyst preparation and molding methods are the same as those in Example 10. The expression of the active composition of the prepared catalyst is as follows:
[0201] Mo x Bi 0.04x Fe 0.16x Ni 0.39x Mg 0.15x R 0.024x Cr(VI) 0.035x Ce(Ⅲ) 0.065x La 0.016x Ru 0.0002x O 4.1x
[0202] The catalyst performance evaluation methods are the same as those in Example 10.
[0203] The active components and performance evaluation results of the catalyst are shown in Table 1.
[0204] Embodiment 15
[0205] Except that the dosage of ruthenium nitrate was reduced by 0.1 g in the composition of the soluble metal salt solution, and 0.1 g of platinum nitrate was added, the other catalyst preparation and molding methods were the same as those in Example 10. The expression of the active composition of the prepared catalyst is as follows:
[0206] Mo x Bi 0.04x Fe0.16x Ni 0.39x Mg 0.15x R 0.024x Cr(VI) 0.035x Ce(Ⅲ) 0.081x Pt 0.0002x O 4.1x
[0207] The catalyst performance evaluation methods are the same as those in Example 10.
[0208] The active components and performance evaluation results of the catalyst are shown in Table 1.
[0209] Example 16
[0210] Except that the composition of the soluble metal salt solution is replaced by 175 g of ferric nitrate nonahydrate, 20 g of bismuth nitrate pentahydrate, 125 g of nickel nitrate hexahydrate, 70 g of magnesium nitrate hexahydrate, 6 g of potassium nitrate, 5 g of chromium nitrate, 5 g of cerium nitrate hexahydrate and 0.4 g of ruthenium nitrate, the other catalyst preparation and molding methods are the same as those in Example 10. The expression of the active composition of the prepared catalyst is as follows:
[0211] Mo x Bi 0.03x Fe 0.31x Ni 0.3x Mg 0.2x K 0.04x Cr(Ⅲ) 0.01x Ce(Ⅲ) 0.01x Ru 0.001x O 4x
[0212] The catalyst performance evaluation methods are the same as those in Example 1.
[0213] The active components and performance evaluation results of the catalyst are shown in Table 1.
[0214] Embodiment 17
[0215] Except that the composition of the soluble metal salt solution is replaced by 140 g of ferric nitrate nonahydrate, 35 g of bismuth nitrate pentahydrate, 130 g of nickel nitrate hexahydrate, 35 g of magnesium nitrate hexahydrate, 5 g of potassium nitrate, 15 g of chromium nitrate, 20 g of cerium nitrate hexahydrate and 0.3 g of ruthenium nitrate, the other catalyst preparation and molding methods are the same as those in Example 10. The expression of the active composition of the prepared catalyst is as follows:
[0216] Mo x Bi 0.05x Fe 0.24x Ni 0.36x Mg 0.1x K 0.03x Cr(Ⅲ) 0.03x Ce(Ⅲ) 0.03xRu 0.0007x O 4x
[0217] The catalyst performance evaluation methods are the same as those in Example 1.
[0218] The active components and performance evaluation results of the catalyst are shown in Table 1.
[0219] Embodiment 18
[0220] Except that the composition of the soluble metal salt solution is replaced by 120 g of ferric nitrate nonahydrate, 40 g of bismuth nitrate pentahydrate, 150 g of nickel nitrate hexahydrate, 25 g of magnesium nitrate hexahydrate, 6 g of potassium nitrate, 2 g of rubidium nitrate, 20 g of chromium nitrate, 35 g of cerium nitrate hexahydrate and 0.2 g of ruthenium nitrate, the other catalyst preparation and molding methods are the same as those in Example 10. The expression of the active composition of the prepared catalyst is as follows:
[0221] Mo x Bi 0.06x Fe 0.21x Ni 0.44x Mg 0.07x K 0.04x R 0.01x Cr(Ⅲ) 0.04x Ce(Ⅲ) 0.06x Ru 0.0004x O 4x
[0222] The catalyst performance evaluation methods are the same as those in Example 1.
[0223] The active components and performance evaluation results of the catalyst are shown in Table 1.
[0224] Embodiment 19
[0225] Except that the composition of the soluble metal salt solution is replaced by 70 g of ferric nitrate nonahydrate, 48 g of bismuth nitrate pentahydrate, 160 g of nickel nitrate hexahydrate, 18 g of magnesium nitrate hexahydrate, 1 g of potassium nitrate, 1 g of cesium nitrate, 30 g of chromium nitrate, 60 g of cerium nitrate hexahydrate and 0.05 g of ruthenium nitrate, the other catalyst preparation and molding methods are the same as those in Example 10. The expression of the active composition of the prepared catalyst is as follows:
[0226] Mo x Bi 0.07x Fe 0.12x Ni 0.5x Mg 0.05x K 0.007x Cs 0.004x Cr(Ⅲ) 0.05x Ce(Ⅲ) 0.1x Ru 0.0001x O 4x
[0227] The catalyst performance evaluation methods are the same as those in Example 1.
[0228] The active components and performance evaluation results of the catalyst are shown in Table 1.
[0229] Embodiment 20
[0230] Except that the carrier liquid is replaced by 500 g of silica sol with a silica content of 30% and 200 g of silica sol with a silica content of 41%, the other catalyst preparation and molding methods are the same as those in Example 10. The active composition of the prepared catalyst is the same as that in Example 10.
[0231] The catalyst performance evaluation methods are the same as those in Example 10.
[0232] The composition and performance evaluation results of the catalyst are shown in Table 1.
[0233] Embodiment 21
[0234] Except that the carrier liquid is replaced with 300 g of silica sol with a silica content of 30% and 400 g of silica sol with a silica content of 41%, the other catalyst preparation and molding methods are the same as those in Example 10. The active composition of the prepared catalyst is the same as that in Example 10
[0235] The catalyst performance evaluation methods are the same as those in Example 10.
[0236] The composition and performance evaluation results of the catalyst are shown in Table 1.
[0237] Embodiment 22
[0238] Except that the carrier liquid is replaced by 200 g of silica sol with a silica content of 30% and 500 g of silica sol with a silica content of 41%, the other catalyst preparation and molding methods are the same as those in Example 10. The active composition of the prepared catalyst is the same as that in Example 10
[0239] The catalyst performance evaluation methods are the same as those in Example 10.
[0240] The composition and performance evaluation results of the catalyst are shown in Table 1.
[0241] Embodiment 23
[0242] Except that the carrier liquid is replaced by 100 g of silica sol with a silica content of 30% and 600 g of silica sol with a silica content of 41%, the other catalyst preparation and molding methods are the same as those in Example 10. The active composition of the prepared catalyst is the same as that in Example 10
[0243] The catalyst performance evaluation methods are the same as those in Example 10.
[0244] The composition and performance evaluation results of the catalyst are shown in Table 1.
[0245] Embodiment 24
[0246] Except that the carrier liquid is replaced by 700 g of silica sol having a silica content of 41%, the other catalyst preparation and molding methods are the same as those in Example 10. The active composition of the prepared catalyst is the same as that in Example 10
[0247] The catalyst performance evaluation methods are the same as those in Example 10.
[0248] The composition and performance evaluation results of the catalyst are shown in Table 1.
[0249] Embodiment 25
[0250] Except that the carrier liquid is replaced by 450 g of silica sol having a silica content of 41%, the other catalyst preparation and molding methods are the same as those in Example 10. The active composition of the prepared catalyst is the same as that in Example 10
[0251] The catalyst performance evaluation methods are the same as those in Example 10.
[0252] The composition and performance evaluation results of the catalyst are shown in Table 1.
[0253] Embodiment 26
[0254] Except that the carrier liquid is replaced by 600 g of silica sol having a silica content of 41%, the other catalyst preparation and molding methods are the same as those in Example 10. The active composition of the prepared catalyst is the same as that in Example 10
[0255] The catalyst performance evaluation methods are the same as those in Example 10.
[0256] The composition and performance evaluation results of the catalyst are shown in Table 1.
[0257] Embodiment 25
[0258] Except that the carrier liquid is replaced by 800 g of silica sol having a silica content of 41%, the other catalyst preparation and molding methods are the same as those in Example 10. The active composition of the prepared catalyst is the same as that in Example 10
[0259] The catalyst performance evaluation methods are the same as those in Example 10.
[0260] The composition and performance evaluation results of the catalyst are shown in Table 1.
[0261] Embodiment 25
[0262] Except that the carrier liquid is replaced by 900 g of silica sol having a silica content of 41%, the other catalyst preparation and molding methods are the same as those in Example 10. The active composition of the prepared catalyst is the same as that in Example 10
[0263] The catalyst performance evaluation methods are the same as those in Example 10.
[0264] The composition and performance evaluation results of the catalyst are shown in Table 1.
[0265] Comparative Example 1
[0266] The active composition of the catalyst provided in Example 5 of Chinese patent document CN101168129B is as follows:
[0267] Mo 12 Bi 0.55 Fe1Ni4Mg3Zn 0.5 Mn 0.5 La 0.2 Ce 0.2 G 0.1 Na 0.05 Cl 0.05 Al 0.05 K 0.05 Cs 0.2 O x +50%SiO2
[0268] The preparation and evaluation methods of the catalyst are similar to those of the embodiments of the present invention.
[0269] The composition and performance evaluation results of the catalyst are shown in Table 1.
[0270] Comparative Example 2
[0271] The active composition of the catalyst provided in Example 5 of Chinese patent document CN101168129B is as follows:
[0272] Mo 10 Bi 0.4 Fe 1.3 Ni6Cr 0.8 Ce 0.4 K 0.2 P 0.2 B 0.2 O x +35%SiO2
[0273] The preparation and evaluation methods of the catalyst are similar to those of the embodiments of the present invention.
[0274] The composition and performance evaluation results of the catalyst are shown in Table 1.
[0275] Comparative Example 3
[0276] The active composition of the catalyst provided in Example 9 of Chinese patent document CN115501882 A is as follows:
[0277] Mo 12 Bi 1.5 Fe 2.7 Ni 5.5 Mg5K 0.8 Nd 2.45 Tm 0.03 Yb 0.02 O x +50%SiO2
[0278] The preparation and evaluation methods of the catalyst are similar to those of the embodiments of the present invention.
[0279] The composition and performance evaluation results of the catalyst are shown in Table 1.
[0280]
[0281]
[0282] Notes:
[0283] 1. The M value is the ratio of the sum of molybdenum and other metal elements in the catalyst system, and its value can reflect the state of the vacancy structure in the catalyst. The M value ranges from 0.88 to 1.2. When the M value is greater than 1 and less than 1.2, it indicates that the molybdenum in the catalyst system is excessive and the activity is reduced; when the M value is less than 1 and greater than 0.88, it indicates that the molybdenum in the catalyst system is missing, but this molybdenum-deficient structure is conducive to the formation of an ion vacancy structure, which increases the transmission rate of lattice oxygen.
[0284] 2. The carrier ratio is the percentage of the carrier to the total mass of the catalyst (excluding water); the carrier solid content represents the mass percentage of silicon dioxide in the carrier silica sol composition.
[0285] 3. The wear index is the percentage of catalyst particles lost between 0 and 5 hours. The wear index is a key indicator of the physical properties of the catalyst of the present invention. A lower wear index means less catalyst is lost in the fluidized bed reactor. The wear rate of commercially available acrylonitrile catalysts is no more than 4%. The determination method of the wear index adopts the internationally accepted test standard.
[0286] Table 1 shows that based on the ratio of different metals in the present invention, the formula composition of the catalyst and the crystal phase structure in the catalyst preparation process are optimized, so that the catalyst prepared by the present invention can not only maintain a high trinitrile product yield for a long time, but also reduce the loss rate of molybdenum-containing substances.
[0287] The above-mentioned ideal embodiments of the present invention are inspirations. Through the above-mentioned description content, relevant personnel can make various changes and modifications without departing from the technical idea of the present invention. These equivalent forms also fall within the scope defined by the claims attached to this application.
Claims
1. An ammonia oxidation catalyst, characterized in that The active component of the catalyst is represented by the general formula Mo x Bi a Fe b A c B d C e D f E g F h O y Indicates that, in this general formula: Mo, Bi, Fe, O represent molybdenum, bismuth, iron and oxygen respectively; A represents at least one element selected from the group consisting of nickel, cobalt, manganese, zinc and cadmium; B represents at least one element selected from the group consisting of alkaline earth metal elements consisting of magnesium, strontium and barium; C represents at least one element selected from the group consisting of alkali metal elements consisting of potassium, rubidium and cesium; D represents at least one element selected from the group consisting of tungsten, vanadium, chromium, gallium, germanium, scandium, yttrium, indium, tin and antimony; E represents at least one element selected arbitrarily from lanthanide elements except promethium; F represents at least one element selected from the platinum group elements; a, b, c, d, e, f, g, h and y are the atomic numbers of Bi, Fe, A, B, C, D, E, F metal elements and oxygen respectively; x is the number of molybdenum atoms, and x is any integer greater than 1, which is used as a reference value; The value of a is a multiple of x, and the multiple range of a is 0.03 to 0.07; b is a multiple of x, and the multiple range of b is 0.12 to 0.31; c is a multiple of x, and the multiple range of c is 0.3 to 0.5; The value of d is a multiple of x, and the multiple range of d is 0.05 to 0.2; The value of e is a multiple of x, and the range of multiples of e is 0.01 to 0.06; The value of f is a multiple of x, and the multiple range of f is 0.01 to 0.05; The value of g is a multiple of x, and the range of multiples of g is 0.01 to 0.1; h is a multiple of x, and the multiple range of h is 0.0001 to 0.001; The value of y is the total number of oxygen atoms required to satisfy the compounds of each element in the catalyst.
2. The ammonia oxidation catalyst according to claim 1, characterized in that The atomic number relationship of each metal element is expressed by the following formula: M = (number of Mo atoms × 2) / (∑ number of atoms of other metal elements × valence of corresponding metal elements) Wherein, M represents the proportional value obtained by dividing the product of the valence number of molybdate and the number of molybdenum atoms by the sum of the corresponding products of the corresponding valence numbers and the number of atoms of the remaining metal components; The value range of M is 0.88~1.
2.
3. The ammonia oxidation catalyst according to claim 1, characterized in that The value of M is 0.93~1.
05.
4. The ammonia oxidation catalyst according to claim 1, characterized in that B is one of magnesium and strontium; C is one of rubidium and cesium; D is one of tungsten and chromium; E is one of lanthanum and cerium; F is one of platinum and ruthenium.
5. The ammonia oxidation catalyst according to claim 1, characterized in that The catalyst further comprises a carrier, and the amount of the carrier used accounts for 40-60wt% of the total mass of the catalyst.
6. A method for preparing an ammonia oxidation catalyst according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: The raw materials of the metal elements constituting the catalyst and the carrier raw materials are mixed in advance to prepare an aqueous slurry, and then the obtained aqueous slurry is dehydrated and dried, and the obtained dry product is roasted to finally obtain a catalyst product.
7. The method for preparing an ammonia oxidation catalyst according to claim 6, characterized in that: The raw materials of the metal elements are selected from the following forms of each metal element: oxide or nitrate, ammonium salt, hydroxide.
8. The method for preparing an ammonia oxidation catalyst according to claim 6, characterized in that: The calcination temperature is 550-650°C, and the calcination time is 2-4h.
9. Use of the ammonia oxidation catalyst according to any one of claims 1 to 5, characterized in that: The catalyst is used in the catalytic ammoxidation reaction of propylene, ammonia and oxygen. Under a certain reaction temperature and reaction pressure, propylene, ammonia and a gas containing molecular oxygen react in a fluidized bed reactor filled with the catalyst to convert propylene into acrylonitrile, acetonitrile, hydrocyanic acid or other related products.
Citation Information
Patent Citations
Catalyst for olefin ammoxidation producing unsaturated nitriles
CN101168129B
Fluidized-bed catalyst for the production of acrylonitrile and process for the production of acrylonitrile
CN101534945B
Fluidized catalyst for acrylonitrile
CN1054914A
Catalysts used in the production of acrylonitrile
CN107282064B
Catalyst for preparing acrylonitrile through propylene ammoxidation as well as preparation method and application of catalyst
CN115501882A
Cited By
Ammoxidation catalyst, and preparation method therefor and use thereof
WO2026109079A1